Assessment of oral hygiene and quality of life of children with autism spectrum disorder and their caregivers: an observational clinical study - Rodrigues, João Victor Soares [UNESP]; Poli, Maria Clara Faria [UNESP]; Cirelli, Thamiris; de Melo Stevanato Nakamune, Ana Cláudia [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Turcio, Karina Helga Leal [UNESP]; da Silva Figueredo, Carlos Marcelo; Theodoro, Leticia Helena [UNESP] (My University, 2024)
Objective: This study aimed to evaluate the degrees of dependence and presence of bacterial plaque in children with autism spectrum disorder (ASD) and the quality of life of children and their caregivers. Method and materials: This was a cross-sectional observational study. This study included 119 individuals with ASD and their caregivers. Data were collected through a sociodemographic questionnaire, WHOQOL-Bref, and Burden interview to measure quality of life and caregiver burden, respectively. The Autoquestionnaire Qualite de Vie Enfant Image questionnaire, adapted in game format, was applied to verify quality of life in children with ASD. An oral clinical examination evaluated the visible plaque index. The collected data were tabulated and organized for statistical analysis with a significance level of 5%. Results: It was observed that 52% of the children had a severity of ASD level 1; 70% were dependent for general activities, and 65% were dependent for oral hygiene. Of the 77 children who thoroughly answered the questionnaire about their quality of life, 64.9% had good quality of life, and 35.1% had scores below 48, that is, low quality of life. In general, the caregivers generally presented quality of life with a rate of 60.95 (good) points on the scale. It was observed that gingival bleeding greater than 30% is two (ASD 2 + ASD 3) to three (ASD 3) times more likely to occur in patients who have higher levels of ASD (P < .004). Conclusion: It was concluded that the quality of life of individuals with ASD was good, that most children are dependent for their daily activities and oral hygiene, and that they showed reasonable plaque control. On the other hand, the caregivers presented low quality of life and moderate burden.
Keywords: autism spectrum disorder; caregivers; observational study; quality of life